Respon Jangka Pendek Pasar Saham Indonesia terhadap Wabah Pandemi Covid-19 - Kristiana Oktavia; Robiyanto Robiyanto; Harijono Harijono (AFRE (Accounting and Financial Review), 2022)
The Indonesian stock market's response to the pandemic Covid-19 outbreak uses the event study method with abnormal return technical tools. This study aims to determine the stock market response to Covid-19, namely responding significantly negative and not because many stocks in other countries were affected by Covid-19. This event study method had carried out observations from 12 days before the announcement to 30 days after the announcement of Covid-19. The results of the data show that the data has no significant effect before and after the announcement by t-statistical analysis. In the significance test with daily observation data, the average abnormal return has no significant effect  before the announcement. Then, after the announcement, the average normal return on the 5th, 8th, 15th, 17th and 26th day responded significantly negative, although not entirely. The results of this study indicate that the response of the Indonesian stock market is significantly negative due to the Covid-19 outbreakDOI: https://doi.org/10.26905/afr.v5i2.7601